(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Allelopathic effect of different concentrations (0, 20, 40 and 60%) of root and leaf extracts of obnoxious weed Argemone mexicana on germination and seedling growth of blackgram, rapeseed and wheat varieties was studied. Percentage of germination and lengths of main root and shoot and seedling dry weight were highly significantly decreased with the increase of both root and leaf extracts. In some cases, root extract was more inhibitory, but in others leaf extract was more inhibitory. Among the varieties, Dhali of rapeseed and Akbar of wheat were most sensitive to the aqueous extract of Argemone Mexicana. Bangladesh J. Sci. Ind. Res. 42(2), 229-234, 2007